TANTANGAN DALAM PELAKSANAAN APLIKASI E - OPEN2.0 PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA BEKASI TAHUN 2026 - Muhamad Rahman; Nunik Retno Herawati (Journal of Politic and Government Studies, 2026)
Digital transformation has encouraged the Bekasi City Government to develop the E - Open2.0 application as a web-based innovation for population administration services. This study aims to analyze the effectiveness of E - Open2.0 in facilitating population administration services, identify implementation challenges from technological, organizational, and environmental perspectives, and examine the efforts of the Bekasi City Department of Population and Civil Registration to address these challenges. This study employed a descriptive qualitative approach using interviews, observations, documentation, and literature review as data collection techniques. Data were analyzed using the Miles and Huberman interactive model. The study applied the Technology–Organization–Environment (TOE) framework developed by Tornatzky and Fleischer and Agus Dwiyanto's Public Service Theory. The findings indicate that E - Open2.0 improves service efficiency and accessibility but still faces challenges related to system disruptions, limited institutional capacity, low digital literacy, and inadequate public outreach. Therefore, continuous system improvement, staff capacity building, and broader public education are essential to optimize digital public services.